Measuring fuel poverty: General considerations and application to German household data - Peter Heindl (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Fuel poverty measurement consists of two independent parts: firstly, the definition of an adequate fuel poverty line, and secondly, techniques to measure fuel poverty. This paper reviews options for the definition of fuel poverty lines and techniques for fuel poverty measurement. Based on household data from Germany, figures that would result from different fuel poverty lines are derived. Different fuel poverty lines yield highly different results with respect to which households are identified as fuel poor. Thus, the choice of the fuel poverty line matters decisively for the resulting assessment. Options for fuel poverty measurement and subgroup comparison are discussed.
Keywords: I32; Q28; Q48; 330; fuel poverty; energy poverty; poverty measurement; Energiearmut; Germany